Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2106/jbjs.n.00449
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Dislocated Midshaft Clavicular Fractures: Plate or Intramedullary Nail Fixation?

Abstract: The patients in the plate-fixation group recovered faster than the patients in the intramedullary nailing group, but the groups had similar results at six months postoperatively and the time of final follow-up. The rate of complications requiring revision surgery was low. Implant-related complications occurred frequently and could often be treated by implant removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 27 publications
4
64
0
2
Order By: Relevance
“…The remaining 7 studies 20 26 were included in this meta-analysis. Of the 7 studies, 1 study 24 was a multicenter randomized controlled clinical trial and 6 were from a single investigational site; all randomized clinical trials enrolled patients with completely displaced midshaft clavicular fractures (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 7 studies 20 26 were included in this meta-analysis. Of the 7 studies, 1 study 24 was a multicenter randomized controlled clinical trial and 6 were from a single investigational site; all randomized clinical trials enrolled patients with completely displaced midshaft clavicular fractures (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias was demonstrated graphically in Figure 2 and summarized in Figure 3 . The randomization technique was mentioned in 5 studies, 21 , 22 , 24 26 and information of allocation concealment was not available for 2 studies. 20 , 23 Blinding was hardly used in open surgery trials and no 1 study was blinded in the assessment of outcome; thus, the term “blinding of outcome assessment” was assessed as “high risk” for all the 7 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The mean time to union in our series was the same as that of Chen et al and comparable with that of conventional plating. 33,35,36,38 In a 2015 meta-analysis of plate versus intramedullary fixation of midshaft clavicle fractures, Zhang et al showed that intramedullary fixation was associated with a reduced surgery time, smaller incision, faster union rate and better shoulder function at six months. Fewer metal-ware complications and re-fracture after metal-ware removal was also noted.…”
Section: Discussionmentioning
confidence: 99%
“…In the interest of brevity we refer to the study protocol and previously reported objective and patient-oriented outcome for full description of in-and exclusion criteria, operative procedures and (functional) outcome parameters. 16,17 A total of 58 patients were enrolled for PF and 62 for IMF. At baseline, there were no differences between the two groups (Table I).…”
Section: Study Populationmentioning
confidence: 99%